Penerapan pembelajaran berdiferensiasi dengan model pembelajaran Project Based Learning untuk Meningkatkan Hasil Belajar siswa SMP Negeri 1 Ngasem kelas VII mata pelajaran IPA - Lestari, Dian Puji; Joharmawan, Ridwan Joharmawan; Purwati, Yuli (Universitas Negeri Malang, 2023)
The learning currently carried out by teachers still generalizes all students, assuming that all students have the same abilities. The Merdeka Curriculum has great hopes of changing the education system in Indonesia to be more enjoyable and adapted to the circumstances of students in each school. One of the efforts in developing the concept of independent learning that is being launched in the current National Education System is differentiated learning (Fitra, 2022). This is in line with the Project Based Learning model which has an end goal in the form of a project. According to a literature review conducted by Wahyuni (2020), differentiated learning can be integrated with several learning models such as Problem Based Learning, Blended Learning's Station Rotation, Project Based Learning and pay attention to students' learning styles. This study aims to improve the learning outcomes of students of SMP Negeri 1 Ngasem using differentiated learning with the Project Based Learning model in science subjects. The type of research conducted uses class action research or continuous experimentation. The instrument for measuring learning outcomes consists of 10 multiple choice questions. The analysis was carried out using quantitative descriptive analysis. The results of the research that has been done show an increase in the completeness of student learning outcomes in each cycle. Learning in Cycle 2 there was an increase in learning outcomes accompanied by an increase in the percentage of completeness that reached the target of the Collaborative PTK completeness criteria.